Między Chinami a Zachodem. Etos pracy jako przejaw nowej odsłony „zderzenia cywilizacji”? - Banach, Wiesław (Człowiek i Społeczeństwo, 2018)
Wiesław Banach, Między Chinami a Zachodem. Etos pracy jako przejaw nowej odsłony „zderzenia cywilizacji”? [Between China and the West. The ethos of work as a manifestation of new version of the „clash of civilizations”] edited by W. Banach, M.A. Michalski, J. Sójka, „Człowiek i Społeczeństwo” vol. XLVI: Między Chinami a Zachodem. Pytanie o źródła chińskiego sukcesu gospodarczego [Between China and the West. An inquiry into the sources of the Chinese economic miracle], Poznań 2018, pp. 121–143, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. The purpose of this article is to compare the Chinese and Western value systems in terms of their suitability for economic development. The author focuses on a very important element of every economic culture which is the work ethos. He understands it as a conviction that only hard and systematic work gives the individual the chance to live in relative prosperity. The ethos of work understood in this way is one of the most basic and common cultural habits. It does not arise spontaneously, that is, in a natural way, but it must be developed and cherished, or cultivated. A comparison of the contemporary Eastern and Western work ethos can be helpful in understanding the causes of China’s economic success and the declining importance of the West. These considerations are carried out in the context of Samuel Huntington’s 25-year-old thesis about the growing importance of cultural factors in the modern world. According to the author of „Clash of civilizations”, such cultural factors as religion, tradition, customs, morality and everything called the system of values are now the source of a deepening global conflict and at the same time increasing economic distance between China and the West.